2021
DOI: 10.3390/ijms22179285
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Deficiency in Hepatocellular Carcinoma Enhances Surveillance of NK-92 through a Modulation of MICA/B

Abstract: Human hepatocellular carcinoma (HCC) is the most common and even worse at prognosis. The patients with HCC which accompanied by other diseases, such as cirrhosis, can be limited in various treatments, such as chemotherapy, not HCC patients without other diseases. NLRP3 inflammasome plays an important role in the innate immune response, but emerging evidence has indicated that the NLRP3 inflammasome is implicated in all stages of cancer development. Various cells express NLRP3 protein through the autocrine or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…In this study, HCC patients showed reduction and impairment in NK cells. Using in vitro co-culture system of NK cell line NK-92 and HCC cells, it has been shown that NLRP3 down-modulation in HCC cells induces lowered expression of metalloproteinase, subsequent to MICA upregulation which in turn increases NK-92 toxicity, through NKG2D binding ( 92 ). This result is further confirmed by exploiting a xenograft mouse model in which NLRP3 knock-out (KO) in HCC cell delays cancer development, reduces metastasis formation, and increases NK cell toxicity, through MICA-NKG2D interaction ( 92 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, HCC patients showed reduction and impairment in NK cells. Using in vitro co-culture system of NK cell line NK-92 and HCC cells, it has been shown that NLRP3 down-modulation in HCC cells induces lowered expression of metalloproteinase, subsequent to MICA upregulation which in turn increases NK-92 toxicity, through NKG2D binding ( 92 ). This result is further confirmed by exploiting a xenograft mouse model in which NLRP3 knock-out (KO) in HCC cell delays cancer development, reduces metastasis formation, and increases NK cell toxicity, through MICA-NKG2D interaction ( 92 ).…”
Section: Introductionmentioning
confidence: 99%
“…The anti-metastatic efficacy of liver NK cells is regulated by the inflammasome pathway. Mice lacking key inflammasome components, such as caspase 1 or caspase 11 ( Ice −/− or Nlrp3 ( Nlrp3 −/− ), have exacerbated CLM after MC38 intrasplenic injection, which supports the requirement of this pathway to suppress CRC growth in this organ [ 171 ]. In particular, IL-18 plays a critical role in inflammasome-mediated immune surveillance against metastasis.…”
Section: Nk Cells and Ilc1 In Crc Liver Metastasismentioning
confidence: 99%
“…Indeed, depletion of NK cells via anti-asialo GM1 antibodies blocks the anti-metastatic effect of IL-18, while specific loss of IL18r on NK cells recapitulates the impairment of immune surveillance found in inflammasome-deficient mice. IL-18 promotes NK cell maturation because the frequencies and numbers of fully mature NK cells (CD11b hi CD27 lo ) significantly decreases in IL-18 −/− mice, but it also regulates FasL surface expression on NK cells, thus impacting on their cytotoxic activity [ 171 ].…”
Section: Nk Cells and Ilc1 In Crc Liver Metastasismentioning
confidence: 99%
“…Lee H. et al reported that the ablation of NLRP3 in HCC SK-Hep1 Luc cells resulted in elevated NK cytotoxicity in an IFN-g-independent mechanism. The involved mechanism constitutes the downregulation of MICA/B, a ligand of the activating NKG2D receptor, by the downregulation of MMP2, MMP9 and MMP14 in mice engrafted with NLRP3 KO(−/−) SK-Hep1 Luc cells [69]. Fatty acid oxidation (FAO) constitutes another process by which NLRP3 influences the HCC TME.…”
Section: The Role Of Nlrp3 In the Shaping Of The Hcc Tumor Microenvir...mentioning
confidence: 99%